Annular pancreas: a clinical, endoscopic, and immunohistochemical study. Issue 1 (January 1989) - Dowsett, J F; Rode, J; Russell, R C
Abstract : A patient with annular pancreas presenting with severe upper abdominal pain is discussed. Endoscopic retrograde cholangiopancreatography (ERCP) was diagnostic, with successful injection of major and minor papillae showing pancreas divisum, an annular duct emptying at the major papilla and changes of severe chronic pancreatitis in all duct systems. Pylorus preserving pancreatoduodenectomy gave complete pain relief. The annulus was shown immunohistochemically to be entirely of ventral gland origin. Chronic pancreatitis was histologically less severe in the dorsal gland. Antegrade dye injection with x-ray showed dorsal to ventral connection in the resected specimen.